Effectiveness of Interpersonal Communication Interaction of Parents to Children in Early Education Planting About Islam in Prapatan Hamlet, Tanak Beak Village, Central Lombok - Nurliya Ni’matul Rohmah (International Consortium of Education and Culture Research Studies, 2020)
This study aims to describe the Effectiveness of Interpersonal Communication Interaction of Parents and Children in Early Education about Islam in Prampuan Hamlet, Tanak Beak Village, Central Lombok. The description is related to parental communication patterns as Madrasatul Ula in the form of interpersonal communication, so that the messages about Islam to children are effectively conveyed. This research is a type of qualitative research with a descriptive approach. The subjects in this study were parental communication patterns and children's behavior as research objects. Data collection methods used which are observation, interviews and documentation. Data analysis techniques using the interactive model of Miles and Huberman include data collection, data reduction, data presentation and verification or drawing conclusions. As for data validation or checking the validity of the data, researchers use source triangulation. The results showed that the Interpersonal Communication Interaction of Parents and Children in Early Education about Islam in Prampuan Hamlet, Tanak Beak Village, Central Lombok was improved effective. This pattern of communication is applied by parents in giving Islamic teachings to children. So that the behavior of children in this Village looks noble and diligent in worship, the factors achieved and the delivery of interpersonal communication of parents to this child are also influenced by the environment and associates.